ӨНДӨР ОРЛОГОТОЙ ИРГЭДИЙН МЕДИА ХЭРЭГЛЭЭ БА ЯЛГААТАЙ БАЙДАЛ - Д.Амгаланбаатар, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Pareto principle or 80-20 rule is the principle that shows as for multi-events 80% of the total results depend only on 20%. In 1906, and Italian economist Wilfredo Pareto noticed that 20% of the population occupy 80% of total territory of Italy. Later, Yosif M.Juran recommended this principle and named after Pareto. Same in business “20% of purchasers make 80% of total sales”. Business organizations and entities focus on How to attract potential customers with high income? How to make them their customers? Therefore, we have tried to study how to attract potential people with high income and their lifestyles. In the framework of the studies on the citizens with high income, we involved of total 300 managerial and entrepreneurs with personal income of 3+ million.